Adsorption of aqueous sulfamethoxazole using iron-impregnated koh-modified biochar from bamboo (Bambusa blumeana) leaves. - Monterde, Vennice Ann
The presence of persistent pharmaceuticals, especially sulfamethoxazole (SMX) in natural bodies of water can cause physiological harm to both humans and animals and have environmental damage. In this study, leaves from bamboo were valorized and synthesized as a novel iron-impregnated KOH-modified biochar (FeKB) to remove SMX in water through adsorption. Biochar was first pyrolyzed at 450℃ for 2 hours, followed by a two-step surface modification: KOH modification to develop a porous structure, and iron impregnation to improve functional groups. The adsorbent was then characterized using SEM-EDS, FTIR, and point of zero charge. SEM-EDS and FTIR verified the modification processes as FeKB developed a porous surface with iron ions on the surface, and essential functional groups were detected. The pHPZC OF FeKB was determined to be 6.80. An adsorption study using 2k full factorial design was conducted to investigate the effects of initial solution pH, initial SMX concentration, and adsorbent dosage. A maximum of 76% SMX removal was obtained at pH 2, 5 mg L-1 SMX, and 3 g L-1 FeKB. it revealed that the primary mechanism for the adsorption of SMX were hydrogen bonding, hydrophobic and 𝛑-𝛑 EDA interactions. The Elovich kinetic model and Redlich-Peterson isotherm model best fitted the experimental data implying involvement chemisorption onto heterogenous surfaces. The Langmuir maximum adsorption capacity obtained in this study was 8.32 mg g-1. Considering the percent removal, adsorption capacity, and resource valorization, FeKB is a promising adsorbent for the adsorptive removal of SMX.